"Oh, By the Way, the Patient is Pregnant!" - Porteous, Joan (Operating Room Nurses Association of Canada Journal, 2008)
Approximately one to three per cent of pregnant women undergo surgery that is unrelated to their pregnancy. In Canada this represents about 5,000 patients each year that present unique challenges to the perioperative nurse and the entire surgical team.